2007
DOI: 10.1158/0008-5472.can-06-1615
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Sendai Virus Particles Eradicate Tumors by Inducing Immune Responses through Blocking Regulatory T Cells

Abstract: UV-inactivated, replication-defective Sendai virus particles [hemagglutinating virus of Japan envelope (HVJ-E)] injected into murine colon carcinoma (CT26) tumors growing in syngeneic BALB/c mice eradicated 60% to 80% of the tumors and obviously inhibited the growth of the remainder. Induced adaptive antitumor immune responses were dominant in the tumor eradication process because the effect was abrogated in severe combined immunodeficient mice. Murine and human dendritic cells underwent dose-dependent maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
161
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(165 citation statements)
references
References 43 publications
2
161
1
1
Order By: Relevance
“…39 We have previously reported that HVJ-E also induces Type I IFN secretion in murine DCs in a fusion-dependent manner, 40 but not in murine cancer cells. 27,28 However, in the culture medium of PC3 cells, significant induction of IFN-a and -b was detected following HVJ-E treatment (Fig. 4a).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…39 We have previously reported that HVJ-E also induces Type I IFN secretion in murine DCs in a fusion-dependent manner, 40 but not in murine cancer cells. 27,28 However, in the culture medium of PC3 cells, significant induction of IFN-a and -b was detected following HVJ-E treatment (Fig. 4a).…”
Section: Resultsmentioning
confidence: 95%
“…[26][27][28] It induces tumor-specific NK cell migration through CXCL10 production by DCs, and enhances NK cell activity through the secretion of IFN from DCs. 28 HVJ-E also enhances DC maturation and activates CTLs against cancer cells by enhancing effector T cells and suppressing regulatory T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intratumoral administration of UV-inactivated, replication-deficient Sendai virus induced a robust antitumoral immune response (including cytotoxic T lymphocyte (CTL) induction, dendritic cell maturation and antagonism of Tregs) and resulted in significant efficacy in CT26 syngeneic murine colorectal cancer model. 48 It will be interesting to study how much of this vaccine effect contributes to antitumoral efficacy in oncolytic Sendai virus studies. A 'vaccine' effect was also seen with parvovirus H-1 in a rat lung tumor metastases model.…”
Section: Genetic Engineering Of Oncolytic Viruses Targets Cancer Signmentioning
confidence: 99%